La representación de la violencia de estado en un episodio de Buscavidas de Carlos Trillo y Alberto Breccia - Cristián Palacios (Les Cahiers ALHIM)
In this work we propose to analyse a chapter of the comic book series Buscavidas by Carlos Trillo and Alberto Breccia as a case especially significant of the way in which the argentine comic book search to define its position against the political violence, and to shed light on it. Is in this particularly complex work where Breccia push over the edge the consequences of the premise How to represent the horror? from which he has produced some of his most revolutionary works. In this work we analyse the last chapter of the series that can operate as a key of reading of the whole work. In this chapter Breccia take up stance not only against history but also against the artistic language itself in which the work is placed. It is an episode especially significant of the way in which the argentine comic book search to define its position against the political violence, and to shed light on it